Digital temples: a shape grammar to generate sacred buildings according to Alberti’s theory - Figueiredo, Bruno (2013)
The research presented further is part of the Digital Alberti research project, which aims to determine the influence of Alberti’s treatise on Architecture, De re aedificatoria, on the Portuguese Renaissance architecture, through the use of a computational framework. One of the project tasks entailed the translation of the treatise’s textual descriptions concerning the morphological, proportional and algorithmic principles of the sacred buildings into a shape grammar. Subsequently a computational model was developed, in order to proceed to the derivation of examples of the same language. This article discusses the use of analytical shape grammars to undertake an architectural analysis, as well as the fact of the source of this grammar and correspondent architectural language to be a text instead of a set of buildings and designs. It reviews the methodology to implement the shape grammar and describes the several stages of development, following the interpretation of treatise into a consistent set of shape rules, by defining their spatial relations, parameters and conditions. It also reviews the implementation of this knowledge into a generative parametric computer program through visual programming language Grasshopper.